Lingkungan Hidup dan Liberalisasi Perdagangan: Upaya Mencari Jalan Tengah - Hartati, Anna Yulia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2007)
Trade liberalization has been claimed as one prime mover of environment degradation. This article discusses the contradiction between environment and trade liberalization. It suggests that in order to met the interest of both of them, the concept of sustainable development can be applied